Penentuan Kualitas Minyak Goreng Bekas Setelah Penambahan Adsorben Alami dari Bonggol Jagung dan Ampas Tebu - Permatasari, Ni Made Ayu Dinda; Hasanah, Nunung Uswatun; Setiawan, Wahyu Aldi; Diba, Asmara Yauma Putri Farah; Sahila, Dinda; Wulandari, Hesti; Muliasari, Handa (UNIVERSITAS MUHAMMADIYAH MATARAM, 2021)
Continuous and repeated use of cooking oil at high temperatures accompanied by air and water contact can result in a hydrolysis reaction. The quality of the oil can be determined by carrying out the procedure for determining the free fatty acid content (FFA). Used cooking oil can be purified using an adsorbent/absorbent. Sugarcane bagasse and corn cobs have been widely used as adsorbents, but there has been no study comparing the increase in oil quality with these two adsorbents. This study aims to compare the color of the used cooking oil immersion with bagasse adsorbent and corncob charcoal adsorbent and determine the value of FFA levels of used cooking oil before and after soaking with bagasse adsorbent and corncob charcoal arsoben. The method used is fatty acid adsorption method and alkalimetric titration. From the observations, it was found that the color of the used cooking oil was fading after soaking with 3 types of adsorbents. The color of the immersion with a mixture of 1:1 adsorbent corncob charcoal and bagasse has the highest brightness level. FFA levels of used cooking oil after soaking also decreased from 0.207% to 0.141%; 0.132 %; and 0.094 %. The FFA content of used cooking oil by immersion in a 1:1 mixture of corn cob charcoal and bagasse was the lowest, which means the oil has the highest quality. It can be concluded that a mixture of 1:1 adsorbent of bagasse and corncob charcoal is the best adsorbent.